Injuries in recreational and competitive surfers: A nationwide study in Portugal - Minghelli, B.; Nunes, C.; Oliveira, R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Surfers are subjected to external factors (ocean currents, wind orientation, wave size, contact with the board and other surfers) that require quick and efficient adaptations, increasing the risk of injury while riding waves. This study aimed to determine the incidence of injuries over a 12-month period in Portuguese surfers and to analyze the associated factors. METHODS: The sample included 1016 Portuguese surfers, aged between 8 and 64 years; 853 (84%) were male. A questionnaire was administered during the stages of the Regional Circuit Surf of Portugal. RESULTS: Three hundred and one (29.6%) surfers had an injury in the previous year, with a total of 398 injuries. There were 1.23 injuries per 1000 hours of surfing. The most common injuries were lacerations (23.5%), located in the knee and leg (16.7%). Impacts of the board (27.1%), and injuries during paddling (17.9%) were the most prevalent injury mechanisms. Competitor surfers presented a higher risk of sustaining surfing-related injuries than recreational surfers (odds ratio=1.81; 95% CI: 1.26-2.62; P=0.002). Individuals who had surfed for less than five years were at 1.65 more risk (95% CI: 1.13-2.39; P=0.009) than those who had surfed for more than 10 years; surfers who trained at least three times a week had 1.42 the risk (95% CI: 1.08-1.87; P=0.011) than those who trained less. CONCLUSIONS: Injuries were frequent among Portuguese surfers, with specific affected body areas, mainly caused by impact with the board. It is necessary to create injury prevention strategies, including specific trainings and the use of protection material.